Pengaruh Kemampuan Kerja terhadap Kinerja Para Medis dengan Komitmen Organisasi sebagai Variabel Intervening pada Puskesmas Kenali Besar - Ratu Febitri; Sumarni Sumarni; Dwi Kurniawan (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
A fundamental component of human resources is the capacity to facilitate corporate objectives and determine whether enhanced competencies might elevate performance. Organizational commitment is crucial as it reflects the allegiance of medical workers to their institution. High devotion among medical workers will result in optimal performance. This research aims to ascertain the impact of work ability on the performance of medical personnel, with organizational commitment serving as an intervening variable at the Kenali Besar Community Health Center. The research methodology employs quantitative descriptive analysis. This research demonstrates that work ability has a favorable and significant impact on the performance of medical personnel. The capacity for work exerts a favorable and substantial impact on organizational commitment. Organizational commitment positively and significantly affects the performance of medical personnel. Work ability exerts a positive and considerable impact on the performance of medical personnel, with organizational commitment serving as an intervening element.